Manajemen Pendidikan Karakter di Universitas Pamulang - Hasanah, Yenny Merinatul; Husnul, Nisak Ruwah Ibnatur (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aimed to describe the implementation of character education management and to find out the barrier factors in implementing the character education at Universitas Pamulang. This research applied qualitative approach. The subjects of this research involved the foundation, rector, team of vice rector III, lecturers, and students of Universitas Pamulang. The technique of data collection was observation, document analyses, and interviews. The technique of data analysis referred to interactive model data analysis, which is triangulation. The findings of the implementation of character education management were as follow: First, the planning to grow shared awareness and to equalize the perception on the importance of value or character integration. Second, organizing the distributions of tasks, authorities, and responsibilities to the whole lecturers, especially the lecturers of religion subject and the team of Vice Rector III. Third, mobilizing the academic, non-academic activities; ways and processes to improve the activities. Fourth, controlling; observing what have been achieved and felt by the implementation of character education by the foundation, rector, all lecturers, team of Vice Rector III, religion subject lecturers, and students. Meanwhile, there was a barrier in implementing the character education management at Universitas Pamulang. This barrier regarding limited human resources that actively implemented the existing programs.